Peningkatan Kesantunan Berbahasa Indonesia: Tulis dan Lisan dalam Literasi di SMPN 43 Padang - Roma Kyo Kae Saniro; M. Yusuf; Alex Darmawan; Syafril Syafril; Rizky Amelya Furqan; Aslinda Aslinda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
The activity aimed to improve the language skills of SMPN 43 Padang students, both written and verbal, in writing letters. It was considered necessary due to problems arising from the impoliteness of some students of junior high school in both oral and written communication for both formal and non-formal situations. The method used in this community service was participatory, planned by the Study Program of Indonesian Literature lecturer of Universitas Andalas. Furthermore, the team visited the service centre through observation and communication with SMPN 43 Padang teachers to look for problems and solutions related to language politeness in the school. After that, the team and teachers collaborated by compiling an agenda for implementing the engagement service. During the implementation stage, the material was presented, followed by the active participation of students through oral and written communication practices. In the final stage, an evaluation was conducted to formulate the main problems and assess subsequent developments after the community service activities. Based on the review carried out through an analysis of student work results, in the form of a comparison before and after receiving the material and engaging in writing practice, this service increased students' Indonesian politeness.